Contributions of Greenland GPS Observed Deformation From Multisource Mass Loading Induced Seasonal and Transient Signals. Issue 15 (5th August 2020) - Li, Wenhao; Shum, C. K.; Li, Fei; Zhang, Shengkai; Ming, Feng; Chen, Wei; Zhang, Bao; Lei, Jintao; Zhang, Qingchuan
Abstract: Global Positioning System (GPS) provides critical geodetic constraints on Earth's elastic response induced by ice and other mass loadings in Greenland. Previous studies focused on long‐term ice mass changes, with relatively fewer studies on transient signals and had used fewer GPS stations. Here we reconstructed 44 Greenland‐wide coastal decadal GPS time series using multichannel singular spectral analysis and quantified the origins of spatiotemporal patterns of transient to seasonal signals. We used an exhaustive list of geophysical processes, including surface mass balance (SMB), atmospheric pressure, continental hydrology, nontidal ocean loading, bedrock thermal expansion, precipitation, runoff, and ice discharge, and identified that most of Greenland's GPS sites exhibit SMB‐induced transient signals during 2012–2015, with maximum displacement reaching 20.45 mm. Analyses of differenced time series between adjacent GPS stations near peripheral glaciers reveal that locally varying seasonal signals are primarily attributable to SMB, followed by atmosphere. Plain Language Summary: Prior studies on Greenland ice sheet mass change mainly focused on long‐term and accelerated signals. However, the effects of multisource geophysical mechanisms on GPS observed transient or abrupt signals are relatively less studied, including quantifying locally varying spatiotemporal patterns between adjacent Global Positioning System (GPS) stations over entire Greenland. In this study, we model crustal displacements caused by an exhaustive list of geophysical mechanisms in Greenland, including atmospheric pressure, continental water storage, nontidal ocean circulation loading, bedrock thermal expansion, surface mass balance, and ice discharge. We then reconstruct the transient signals from 44 Greenland‐wide coastal GPS decadal records using multichannel singular spectral analysis. The differenced time series between adjacent GPS stations located near the peripheral glaciers reveals that locally varying deformation is primarily caused by surface mass balance loading, followed by atmosphere loading. Most of GPS observed transient signals are attributable to surface mass balance and ice discharge loading, 2009 to mid‐2011, and 2012 to 2015, which can reach a maximum displacement of 20.5 mm, with a mean displacement of 5.97 mm. Key Points: Interpretation of Greenland‐wide 44 GPS deformation time series, manifested by multisource seasonal and transient mass loading signals We use M‐SSA reconstructed Greenland GPS and modeled deformation data to quantify origins of spatiotemporal loading patterns Differenced GPS time series between adjacent sites reveals that locally varying seasonal signals are primarily attributable to SMB